Factoring governance risk into investor's expected rates of return by means of a weighted average governance index - Rodolfo Apreda (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2007)
Although global investors have been paying more heed than ever to Corporate Governance for the last decade, the evolving premium risk stemming from variegated governance issues has not been factored yet into the expected return of any investor's portfolio. From a theoretical standpoint, this paper sets forth firstly a weighted-average index built up by choosing distinctive and relevant governance variables that go beyond provisions usually embedded in the founding charter. Afterwards, a measure of governance risk premium will be derived out of the index rate of change. Lastly, it will be introduced a multiplicative model of expected returns with a risk adjustment factor over the risk-free asset comprising systematic, nonsystematic, country and governance risk premiums.
Keywords: G11; G34; G12; 330; governance risk; governance index; governance rate; expected return; risk adjustment; Portfolio-Management; Corporate Governance